Lightweight MgB2 wires with a high temperature aluminum sheath made of variable purity Al powder and Al2O3 content. (25th June 2018) - Kováč, P; Hušek, I; Kulich, M; Kováč, J; Melišek, T; Kopera, L; Perez, N; Haessler, W; Balog, M; Krížik, P; Berek, D
Abstract: The properties of high temperature aluminum (HITEMAL, hereinafter HIT) composites made of powders with different particle sizes ranging from 0.8–3 μ m and purities of 99.9%–99.996% were tested. The thermal, electrical, and mechanical properties of these materials were examined and compared with pure Al. Three different HIT materials were used for the outer sheath of single-core MgB2 wires with a Ti barrier manufactured by internal magnesium diffusion into a boron process. The critical currents, thermal stability, and strain tolerances of the MgB2 /Ti/HIT wires were measured at liquid He temperature. It was found that the Al powder purity and particle size used for HIT affect the performance of MgB2 wires. A sheath made of high purity Al powder allows better thermal stability of MgB2 wire, but the strain tolerance is lower in comparison to the wire with HIT made of less pure powder and higher Al2 O3 content. The presented wire configurations are promising for lightweight, thermally stabile, and strain tolerant superconducting MgB2 wires.